Effect of Computer Assisted Instructional (Cai) Package on Senior Secondary School Students’ Achievement in Mathematics: A Post- Covid Sustainable Development in Nigeria. - Okwuoza, Sylvester Orobosa; Olajumoke., Ale Florence (Journal of Education and Practice, 2023)
Purpose: This study investigated the effects of Computer Assisted Instructional (CAI) Package on senior secondary school students' achievement in Mathematics: A post-Covid Sustainable Development in Nigeria. Methodology: The research design adopted was quasi-experimental research design. The sampling technique was multi stage sampling techniques. One hundred and seventy-eight (178) SS2 students comprising 90 male and 88 female students served as sample size. The research instrument was Mathematics Achievement Test (MAT). The reliability of the test instrument was determined using the Pearson product moment correlation analysis formula. A correlation coefficient of 0.86 was obtained which was considered high and suitable for gathering data. The instrument was certified to have face and content validity by expert opinion. Descriptive statistic such as Mean and Standard deviation were used to answer research questions, while t-test was used to test hypotheses at 0.05 significant levels. Findings: The findings among others revealed that students taught mathematics using Computer Assisted Instructional (CAI) Package achieved more than that taught mathematics using the conventional method of teaching. Unique contribution to theory, policy and practice: This study recommended that the use of CAI enhances Achievement of Students in Mathematics especially during post COVID era; therefore, teachers should be discouraged from the use of conventional method of teaching Mathematics but rather to embrace teaching Mathematics using Computer Assisted Instructional (CAI) package on Senior Secondary School Students' Achievement in Mathematics and Post- COVID Sustainable Development in Nigeria.